Changing teachers' TPACK and design beliefs through the Scaffolded TPACK Lesson Design Model (STLDM). (3rd July 2017) - Chai, Ching Sing; Koh, Joyce Hwee Ling
ABSTRACT: This study investigates the change in teachers' design beliefs and their development of technological pedagogical content knowledge (TPACK) through a course designed with the Scaffolded TPACK lesson design model. To achieve these aims, an adapted scale for teachers' design beliefs and TPACK is created and validated. The study reveals significant changes in the teachers' TPACK with large effect size and changes in teachers' design beliefs with medium or small effect size. Further investigation also reveals that the teachers' design beliefs that are constituted by the factors of Beliefs about New Culture of Learning (BNCL), Teachers as Designer (TAD), and their Design Dispositions (DD) predict their TPACK both in first- and second-order structural equation models. The findings may suggest that it is advisable to develop teachers' design beliefs as teacher educators attempt to develop preservice teachers' TPACK.